Structural sequences are conserved in the genes coding for the alpha, alpha' and beta-subunits of the soybean 7S seed storage protein. - Schuler, M A (1982)
Cloned DNAs encoding four different proteins have been isolated from recombinant cDNA libraries constructed with Glycine max seed mRNAs. Two cloned DNAs code for the alpha and alpha'-subunits of the 7S seed storage protein (conglycinin). The other cloned cDNAs code for proteins which are synthesized in vitro as 68,000 d., 60,000 d. or 53,000 d. polypeptides. Hybrid selection experiments indicate that, under low stringency hybridization conditions, all four cDNAs hybridize with mRNAs for the alpha and alpha'-subunits and the 68,000 d., 60,000 d. and 53,000 d. in vitro translation products. Within three of the mRNA, there is a conserved sequence of 155 nucleotides which is responsible for this hybridization. The conserved nucleotides in the alpha and alpha'-subunit cDNAs and the 68,000 d. polypeptide cDNAs span both coding and noncoding sequences. The differences in the coding nucleotides outside the conserved region are extensive. This suggests that selective pressure to maintain the 155 conserved nucleotides has been influenced by the structure of the seed mRNA. RNA blot hybridizations demonstrate that mRNA encoding the other major subunit (beta) of the 7S seed storage protein also shares sequence homology with the conserved 155 nucleotide sequence of the alpha and alpha'-subunit mRNAs, but not with other coding sequences.